Network pharmacology study on the active components of Pterocypsela elata and the mechanism of their effect against cerebral ischemia - Niu B; Zhang H; Li C; Yan F; Song Y; Hai G; Jiao Y; Feng Y (Dove Medical Press, 2019)
Bingxuan Niu,1 Hui Zhang,1 Chunyan Li,2 Fulin Yan,1,2 Yu Song,1 Guangfan Hai,1 Yunjuan Jiao,3 Yansheng Feng31College of Pharmacy, Xinxiang Medical University, Xingxiang, Henan Province 453003, People’s Republic of China; 2Sanquan College of Xinxiang Medical University, Xinxiang, Henan Province 453002, People’s Republic of China; 3Basic Medical College, Xinxiang Medical University, Xinxiang, Henan Province 453003, People’s Republic of ChinaCorrespondence: Fulin YanCollege of Pharmacy, Xinxiang Medical University, 601 Jinsui Avenue, Hongqi District, Xingxiang, Henan Province 453003, People’s Republic of ChinaTel +1 378 251 3326Email yannz2009@163.comObjective: The aim of this study was to identify the active anti-ischemic components of Pterocypsela elata (P. elata) using a network pharmacology approach to construct an effective component anti-cerebral ischemic target network and systematically analyze this medicinal material.Methods: Pharmacological studies have shown that P. elata has an obvious effect against cerebral ischemia. To identify the potential targets, 14 components of P. elata were docked to each structural element of the targets in the DRAR-CPI database by reverse docking technology. We then compared the identified potential targets with FDA-approved targets for stroke/cerebral infarction treatment in the DrugBank database and identified the active components of P. elata and their potential targets for stroke/cerebral infarction treatment. The active component-target networks were constructed using Cytoscape 3.5.1 software. The target protein-protein interactions were analyzed using the STRING database. KEGG pathway analysis and gene ontology (GO) enrichment analysis were performed through the Database for Annotation, Visualization and Integrated Discovery (DAVID).Results: There were 14 active components identified from P. elata and 21 potential targets identified for cerebral ischemia treatment, including carbonic anhydrase 2, ribosyldihydronicotinamide dehydrogenase, cholinesterase, and glutathione S-transferase P. The main involved pathways include metabolic pathways, complement and coagulation cascades and steroid hormone biosynthesis.Conclusion: Through a network pharmacology approach, we predicted the active components of P. elata and their potential targets for cerebral ischemia treatment. Our results provide new perspectives and clues for further studies on the anti-cerebral ischemia mechanism of P. elata.Keywords: network pharmacology, Pterocypsela elata, cerebral ischemia, molecular docking